2022
DOI: 10.3390/ijms23179904
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Exposure to Cigarette Smoke Extract Impedes Skeletal Development and Evokes Craniofacial Defects in Zebrafish

Abstract: Exposure to cigarette smoke represents the largest source of preventable death and disease in the United States. This may be in part due to the nature of the delayed harmful effects as well as the lack of awareness of the scope of harm presented by these products. The presence of “light” versions further clouds the harmful effects of tobacco products. While active smoking in expectant mothers may be reduced by educational and outreach campaigns, exposure to secondhand smoke is often involuntary yet may harm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…An alternative explanation might be that nicotine needs to be metabolized to exert its toxic functions, similar to B(a)A. In line with this notion is a recent study that identified craniofacial defects in developing zebrafish upon nicotine exposure [ 90 ], a phenotype similar to that identified by us in zebrafish upon exposure to aqueous smoke extracts [ 18 ]. These facts may help to resolve the discrepancy between its contradicting cytotoxicity results and explain why cell viabilities were maintained throughout all tested concentrations in both the adult fibroblast and the immature, unspecified stem cells.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…An alternative explanation might be that nicotine needs to be metabolized to exert its toxic functions, similar to B(a)A. In line with this notion is a recent study that identified craniofacial defects in developing zebrafish upon nicotine exposure [ 90 ], a phenotype similar to that identified by us in zebrafish upon exposure to aqueous smoke extracts [ 18 ]. These facts may help to resolve the discrepancy between its contradicting cytotoxicity results and explain why cell viabilities were maintained throughout all tested concentrations in both the adult fibroblast and the immature, unspecified stem cells.…”
Section: Discussionmentioning
confidence: 71%
“…Bones are often hypomineralized, as evidenced by lower bone mineral density and bone mineral content, for example, in the head; consequently, the risk of fracture following minor injuries is increased [ 14 , 15 , 16 , 17 ]. We have recently been able to model these human epidemiological phenotypes in developing zebrafish, which exhibited hypomineralization in multiple bones, alterations to cartilage architecture, and spinal deformations in response to tobacco exposure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…They reveal developmental abnormalities, reduced survival rates, and adverse behavioral effects [ 59 , 60 ], providing insights into nicotine-related diseases, craniofacial defects, and behavioral impacts. This underscores their potential in studying the health risks associated with e-cigarette usage [ 61 , 62 ].…”
Section: Zebrafish As a Versatile Model For Health Researchmentioning
confidence: 99%
“…Therefore, pertinent studies exclusively examining a single component fall short of representing the global effects of tobacco pollutant exposure on embryos [16]. Moreover, although studies using tobacco pollutant mixture have been conducted, most have focused on visible embryonic developmental toxicity, such as malformations, with a limited exploration into the speci c molecular mechanisms involved in these processes [17,18]. Therefore, studying possible underlying molecular mechanisms and the overall effects of tobacco smoke exposure on embryonic development can address the limitations of existing studies and help in the formulation of new and effective preventive measures during pregnancy.…”
Section: Introductionmentioning
confidence: 99%